Inhibition of CPAP–tubulin interaction prevents proliferation of centrosome‐amplified cancer cells. (10th December 2018) - Mariappan, Aruljothi; Soni, Komal; Schorpp, Kenji; Zhao, Fan; Minakar, Amin; Zheng, Xiangdong; Mandad, Sunit; Macheleidt, Iris; Ramani, Anand; Kubelka, Tomáš; Dawidowski, Maciej; Golfmann, Kristina; et al.
Abstract: Centrosome amplification is a hallmark of human cancers that can trigger cancer cell invasion. To survive, cancer cells cluster amplified extra centrosomes and achieve pseudobipolar division. Here, we set out to prevent clustering of extra centrosomes. Tubulin, by interacting with the centrosomal protein CPAP, negatively regulates CPAP‐dependent peri‐centriolar material recruitment, and concurrently microtubule nucleation. Screening for compounds that perturb CPAP–tubulin interaction led to the identification of CCB02, which selectively binds at the CPAP binding site of tubulin. Genetic and chemical perturbation of CPAP–tubulin interaction activates extra centrosomes to nucleate enhanced numbers of microtubules prior to mitosis. This causes cells to undergo centrosome de‐clustering, prolonged multipolar mitosis, and cell death. 3D‐organotypic invasion assays reveal that CCB02 has broad anti‐invasive activity in various cancer models, including tyrosine kinase inhibitor (TKI)‐resistant EGFR‐mutant non‐small‐cell lung cancers. Thus, we have identified a vulnerability of cancer cells to activation of extra centrosomes, which may serve as a global approach to target various tumors, including drug‐resistant cancers exhibiting high incidence of centrosome amplification. Synopsis: Centrosome amplification is frequently observed in human tumors yet cancer cells manage to circumvent cell death by centrosome clustering and generation of a pseudo‐bipolar spindle. Here, genetically perturbing interaction between centrosomal‐P4.1‐associated protein (CPAP) and tubulin in extra‐centrosome‐containing cancer cells is found to activate centrosomes before the onset of mitosis thereby selectively inducing mitotic catastrophe. The CPAP‐tubulin interaction is a cancer cell‐specific target. The small‐molecule compound CCB02 inhibits CPAP‐tubulin interaction, binding at the CPAP binding site of β‐tubulin. Inhibition of CPAP‐tubulin interaction is sufficient to enhance pericentriolar material recruitment and activate extra centrosomes. Extra‐centrosome activation prevents centrosome clustering and reduces proliferation of centrosome amplified cancer cells in vitro and tumorigenesis in vivo . Abstract : Nucleation of microtubules from extra centrosomes can be selectively impaired by the small molecule CCB02, suppressing cell cycle progression and survival of malignant cells.